PENERAPAN MODEL CREATIVE PROBLEM SOLVING (CPS) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SEKOLAH DASAR - Ananda Pazila; Fadhilaturrahmi; Yanti Yandri Kusuma; Zulfah; Rusdial Marta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this research is the low problem-solving ability of students in mathematics lessons in class V. This study aims to improve mathematical problem solving skills in class V UPT SDN 005 Binuang. This research is a classroom action research, which is carried out in two cycles and each cycle consisted of two meetings. The subjects in this study were 1 teacher and 23 students, while the object was using the Application of the Creative Problem Solving (CPS) Model to Improve Mathematical Problem Solving Skills in Elementary Schools. The research instruments consist of teacher activity observation sheets, student activity observation sheets, documentation sheets, and test sheets during the learning process using the Creative Problem Solving (CPS) Model Application. while the data analysis techniques used are qualitative analysis and quantitative analysis. Based on the results of the research that has been carried out through 2 cycles, in cycle I meeting 1 the number of students who completed was 9 students (39.13%) with a very lacking category, and in cycle I meeting 2 the number of students who completed was 13 students (56.52%) with a lacking category. In cycle II, meeting 1, the number of students who completed increased by 17 students (73.91%) with a sufficient category, and in cycle II, meeting 2, the number of students who completed increased by 19 students (82.60%) with a good category. Based on the results of this study, it shows that implementing the Creative Problem Solving (CPS) Model can improve the mathematical problem solving abilities of class V students at UPT SDN 005 Binuang.